Research on the Relationship Between Enterprise Green Transformation and Financial Performance Under the Background of "Double-Carbon" - Guo, Huanyu (International Journal of Global Economics and Management, 2024)
Under the background of "double carbon", green development has become an important direction of manufacturing enterprises. Taking Company A as an example, this paper analyzes the strategic measures of each stage of the green transformation of enterprises, in order to study the impact of the green transformation on the financial performance of enterprises. The results show that: (1) the green transformation of enterprises can be divided into traditional development period, green transformation period and green development period, and different in different stages.(2) Enterprises can effectively improve their profitability and operating ability through green transformation, but the financial performance caused by the transformation lags behind; (3) merger and acquisition and innovation are the main ways for enterprises to achieve rapid green growth quickly. Based on the characteristics of the three stages of green transformation, enterprises should timely pay attention to the adaptation of their own development strategy and the macro environment, and actively seek for green transformation.